Digital financial inclusion and agricultural modernization development in China—a study based on the perspective of agricultural mechanization services - Yingzheng Yan; Liupeng Chen; Ziwei Zhou; Yuanzhu Wei (Humanities & Social Sciences Communications)
Abstracts Enhancing the level of agricultural mechanization services in all countries is essential to guarantee global food security and improve rural pollution. This paper empirically analyzes the impact of Digital Financial Inclusion on the level of agricultural mechanization services in rural areas using a fixed-effects model based on the collection of Chinese provincial panel data from 2011 to 2022. The research in this paper will provide policy recommendations for the modernization of agriculture and the development of inclusive finance in various countries worldwide. After analyzing this paper, the following conclusions are drawn: 1. the development of digital inclusive finance can effectively improve the use of agricultural mechanization services in rural areas. 2. the level of human capital has a moderating role between the two. 3. There is a threshold effect between Digital Financial Inclusion and agricultural mechanization services. 4. There is heterogeneity in the impact of Digital Financial Inclusion on agricultural mechanization services.